Analysis of Risks and Security Requirements in Public Cloud - Banushri, A; A. Karthika, R (International Journal of Engineering and Technology, 2018)
To enjoy the full benefits of cloud computing, it is necessary to have built-in security, privacy, compliance and legal requirements for the cloud implementation and use. Each industry has its own risk levels that it could work within. A company, which is planning to use public cloud services, should be conscious of the regulations and industry risks and need to monitor it and abide by the same. This is due to multi-tenant and open to all nature of public cloud. A thorough risk analysis must be done initially with a public cloud provider. The main objective is to identify the existing vulnerabilities and to implement the measures to counter those threats. There are a variety of risks such as vendor lock-in, non-compliance, poor provisioning, unauthorized access, loss of control, Service Level Agreement (SLA) violations, Internet attacks, etc. To alleviate the risks, there are several measures that could be deployed. This paper deals with mitigation mechanism, security requirements and various risks associated with public cloud.Â Â